Synergistic SERS enhancement and in situ monitoring of photocatalytic reactions in a plasmonic metal/ferroelectric hybrid system by the light-induced pyroelectric effect. Issue 26 (23rd June 2022) - You, Daotong; Wang, Ru; Xie, Jiwei; Liu, Lei; Li, Kaiwei; Han, Xile; Guo, Tuan; Xu, Chunxiang
Abstract : Pyroelectric electric fields-modulated SERS substrate based on Ag nanowires–BiFeO3 /carbon nanofibers enables vibration-free nanogenerators and miniaturizes E-SERS measurements. Abstract : The pyroelectric effect converts thermal energy into usable electrical energy. It is an ideal and effective strategy to enhance the surface-enhanced Raman scattering (SERS) detection sensitivity by tuning the electromagnetic fields. In this work, a plasmonic metal/ferroelectric hybrid SERS substrate was fabricated by integrating a pyroelectric functional layer composed of BiFeO3 with an electron/heat conduction layer of carbon nanofibers (CNFs) using the electrospinning technique. The initial layer was followed by a plasmonic layer of Ag nanowires, which were uniformly spin-coated on BiFeO3 /CNFs. By introducing periodically switched near-infrared (NIR) light, the BiFeO3 /CNFs could effectively convert the thermal energy induced by light into pyroelectric charge, which could adjust the electron densities of Ag, and in turn boost the electromagnetic fields at the "hot spots". The hybrid Ag–BiFeO3 /CNFs were used to test the Raman signals of methylene blue (MB), and a 5.6-fold enhancement of the SERS signal was achieved compared with that noted without the pyroelectric effect and the following parameters were obtained: an ultra-low detection of 10 −13 M, a high enhancement factor of 8.3 × 10 9, and excellent reproducibility with an RSD of 4.08%. The theoretical calculations revealed that the excellent sensitivity was mainly ascribed to the synergistic light-induced pyroelectric and plasmon effects. In addition, this substrate was also used for the detection of ciprofloxacin (CIP) in milk with a limit of detection as low as 10 −10 M. Furthermore, the Ag–BiFeO3 /CNFs were used to successfully in situ monitor the photocatalytic reduction of p -nitrophenol ( p -NTP) to 4, 4′-dimercaptoazobenzene (DMAB) by SERS in real time. This work provides an efficient strategy to develop highly sensitive SERS substrates through pyroelectric-plasmonic hybrid structures, and opens a new avenue for the development of energy harvesters that can be used for extensive applications.